Stereochemistry and Conformation of Skyllamycin, a Non‐Ribosomally Synthesized Peptide from Streptomyces sp. Acta 2897. Issue 17 (12th March 2014) - Schubert, Vivien; Di Meo, Florent; Saaidi, Pierre‐Loïc; Bartoschek, Stefan; Fiedler, Hans‐Peter; Trouillas, Patrick; Süssmuth, Roderich D.
Abstract Skyllamycin is a non‐ribosomally synthesized cyclic depsipeptide from Streptomyces sp. Acta 2897 that inhibits PDGF‐signaling. The peptide scaffold contains an N‐terminal cinnamoyl moiety, a β‐methylation of aspartic acid, three β‐hydroxylated amino acids and one rarely occurring α‐hydroxy glycine. With the exception of α‐hydroxy glycine, the stereochemistry of the amino acids was assigned by comparison to synthetic reference amino acids applying chiral GC‐MS and Marfey‐HPLC analysis. The stereochemistry of α‐hydroxy glycine, which is unstable under basic and acidic conditions, was determined by conformational analysis, employing a combination of data from NOESY‐NMR spectroscopy, simulated annealing and free MD simulations. The simulation procedures were applied for both R‐ and S‐configured α‐hydroxy glycine of the skyllamycin structure and compared to the NOESY data. Both methods, simulated annealing and free MD simulations independently support S‐configured α‐hydroxy glycine thus enabling the assignment of all stereocenters in the structure of skyllamycin and devising the role of two‐component flavin dependent monooxygenase (Sky39) as S‐selective.